Cryptography on Audio Files Using the Blowfish Algorithm - Nuniek Fahriani; Onny Kartika Waluya (Fakultas Teknik Universitas Bhayangkara, 2018)
Blowfish is a 64-bit block cipher with variable key length. The algorithm consists of two part: Key expansion anddata encryption. Allowing its use in cryptography. In general, cryptography is about constructing and analyzecommunication protocols that can block an opponent. Various aspects of information security, Such as confidentialdata, Data integrity, Authentication and non repudance Is the center of modern cryptography. This caseimplementation with encryption and decryption techniques on audio files using java programming, aims to securethe audio data contained in it can be maintained and can only be read by user who have the cryptographic key.